Phytochemical diversity of Eremostachys laciniata Bunge populations in Iran - A Hadipour; M Azizi; H Naghdi-Badi; J Panahandeh; A Delazar; H Aroei (Institue of Medicinal Plants, ACECR, 2016)
Background: Eremostachys laciniata is known as "Chelle-Daghi" in Iran and its rhizomes are used as an emollient to relieve rheumatoid arthritis. Objective: A phytochemical study was performed on 15 populations of Eremostachys laciniata to qualify the phytochemical variations. Methods: Plants collected from their natural habitats and dried rhizomes of E. laciniata were milled and then Soxhlet-extracted by MeOH, and then total phenols were determined calorimetrically by the Folin-ciocalteau reagent and iridoid glycosides were measured by TLC method. Results: The results of MeOH extracts showed that the highest amount with 14.85 gr/plant was obtained in the Areshtanab population. The populations had a significant effect on total phenolic concentrations (p < 0.001) and the Areshtanab with 0.281 mg GAE/g DW had higher phenolic levels than other populations. The results of TLC of iridoids showed that 15 populations had about 11 iridoids components. Cluster analysis by using Wardchr('39')s method detected that the studied populations of E. laciniata were separated into three different groups. Conclusion: In summary, higher values of the total phenols and iridoids in the Areshtanab, Malek-Kian, and Til populations were considered to indicate higher levels of phytochemical heterogeneity and significant diversity between populations, which could be used to domesticate and develop the breeding programs.